Elucidating the origin of chiroptical activity in chiral 2D perovskites through nano-confined growth - Ma Sunihl; Jung Young-Kwang; Ahn Jihoon; Kyhm Jihoon; Tan Jeiwan; Lee Hyungsoo; Jang Gyumin; Lee Chan Uk; Walsh Aron; Moon Jooho (Nature Publishing Group, 2022)
Chiral perovskites are being extensively studied as a promising candidate for spintronic- and polarization-based optoelectronic devices due to their interesting spin-polarization properties. However, the origin of chiroptical activity in chiral perovskites is still unknown, as the chirality transfer mechanism has been rarely explored. Here, through the nano-confined growth of chiral perovskites (MBA(2)PbI(4(1-x))Br(4x)), we verified that the asymmetric hydrogen-bonding interaction between chiral molecular spacers and the inorganic framework plays a key role in promoting the chiroptical activity of chiral perovskites. Based on this understanding, we observed remarkable asymmetry behavior (absorption dissymmetry of 2.0 x 10(-3) and anisotropy factor of photoluminescence of 6.4 x 10(-2) for left- and right-handed circularly polarized light) in nanoconfined chiral perovskites even at room temperature. Our findings suggest that electronic interactions between building blocks should be considered when interpreting the chirality transfer phenomena and designing hybrid materials for future spintronic and polarization-based devices.,In this study, Ma et al. demonstrated that asymmetric hydrogen-bonding interaction between chiral organic spacer and inorganic frameworks plays a key role in promoting the chiroptical activity of chiral perovskites.,